"Have you heard the one about…" using comedy to tackle mental health-related stigma with UK military personnel?. Issue 1 (20th March 2017) - Twardzicki, Maya; Jones, Norman
Abstract : Purpose: The purpose of this paper is to provide first-hand reflections from a public mental health specialist, on developing an innovative comedy-based arts and health project that engaged with UK military personnel. Design/methodology/approach: Project partners included the Academic Department of Military Mental Health at King's College London and Army Headquarters. The project used a repeat measures design. The intervention group (IG) received a mental health-focussed comedy show and the control group received a standard comedy show. Serving Armed Forces personnel participated in focus groups to inform show scripts, which also contained key mental health messages agreed by the project team. Evaluation questionnaires were given out before and after the show and three months later. Findings: The comedy show format proved to be an acceptable/popular way to present mental health-related messages. Post-show there was a statistically significant reduction in mental health stigmatisation and significantly better mental health and stigma-related knowledge in the IG. Research limitations/implications: Due to deployment, follow-up participation was limited, reducing the ability to assess whether the effects were durable. Practical implications: The challenges of working with serving personnel are outlined and some recommendations made to improve future comedy interventions/research with this group. Originality/value: This study provides a thorough evaluation of an arts and health intervention using a comprehensive survey methodology.